2015
DOI: 10.1186/s13104-015-1242-5
|View full text |Cite
|
Sign up to set email alerts
|

Agreement with evidence for tissue Plasminogen Activator use among emergency physicians: a cross-sectional survey

Abstract: BackgroundEmergency department staff play a crucial role in the triage of stroke patients and therefore the capacity to deliver time-dependent treatments such as tissue Plasminogen Activator. This study aimed to identify among emergency physicians, (1) rates of agreement with evidence supporting tissue Plasminogen Activator use in acute stroke care; and (2) individual and hospital factors associated with high agreement with evidence supporting tissue Plasminogen Activator use.MethodsAustralian fellows and trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Overcoming clinician ‘mindlines’ and beliefs about the evidence is a vexing challenge in implementation science [ 28 ] and in acute stroke management. This is particularly so in relation to the administration of thrombolysis, a key nursing and medical responsibility [ 29 , 30 ] and a protocol element with clear evidence of effectiveness [ 4 , 5 ]. As stated by some interviewees, bias against the use of tissue Plasminogen Activator in some sites, also resulted in low acceptance of other elements of the T 3 clinical protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overcoming clinician ‘mindlines’ and beliefs about the evidence is a vexing challenge in implementation science [ 28 ] and in acute stroke management. This is particularly so in relation to the administration of thrombolysis, a key nursing and medical responsibility [ 29 , 30 ] and a protocol element with clear evidence of effectiveness [ 4 , 5 ]. As stated by some interviewees, bias against the use of tissue Plasminogen Activator in some sites, also resulted in low acceptance of other elements of the T 3 clinical protocols.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of normalisation process theory, an individual appraisal by clinicians of the applicability of the evidence to the ED setting worked against the collective action needed to facilitate use and to normalise the use of the protocols in the ED. Other recent research has shown that ED clinicians express low agreement with the evidence supporting tissue Plasminogen Activator use in acute stroke [ 29 , 30 ]. It is therefore possible that active and ongoing championing by key medical staff might have helped to reinforce the education given about the evidence that was part of the implementation strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey items were selected from the previously published literature on behavior change and implementation of evidence-based practice. In addition, the National Stroke Foundation’s Clinical Guidelines for the management of Stroke and its recommendation for hospital facilities and evidence for intravenous thrombolysis was also considered to finalize the survey items [24, 25]. The survey items were also piloted by a team of behavioral researchers, stroke clinicians, emergency physicians, and stroke nurses at the University of Newcastle and the Hunter New England Local Health District [26].…”
Section: Methodsmentioning
confidence: 99%
“…Attitudinal items were developed from literature regarding knowledge implementation 31 and a prior survey. 35,37 Respondents were asked to rate agreement with a series of statements. Participants were asked to rate their level of agreement with each survey item using a four-point scale of ‘strongly disagree’, ‘disagree’, ‘agree’ and ‘strongly agree’ with a ‘not applicable’ option.…”
Section: Methodsmentioning
confidence: 99%